Banks' structural power and states' choices over what structurally matters: The geo-economic foundations of state priority towards banking in France, Germany and Spain - Elsa Clara Massoc (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
Since the 2008 financial crisis, European largest banks' size and business models have largely remained unchallenged. Is that because of banks' continued structural power over States? This paper challenges the view that States are sheer hostages of banks' capacity to provide credit to the real economy - which is the conventional definition of structural power. Instead, it sheds light on the geo-economic dimension of banks' power: key public officials conceive the position of "their own" market-based banks in global financial markets as a crucial dimension of State power. State priority towards banking thus result from political choices over what structurally matters the most for the State. Based on a discourse analysis of parliamentary debates in France, Germany and Spain between 2010 and 2020 as well as on a comparative analysis of the implementation of a special tax on banks in the early 2010s, this paper shows that State's Finance ministries tend to prioritize geo-economic considerations over credit to firms. By contrast, Parliaments tend to prioritize investment. Power dynamics within the State thus largely shape political priorities towards banking at the domestic and international levels.
urn:nbn:de:hebis:30:3-616658
Keywords: 330; structural power; States; banks; geo-economics; institutions